Public opinion on cash transfers for children and adolescents in Argentina: Nine out of ten people support greater adequacy - Blofield, Merike (2023)
Child poverty is a multidimensional challenge and decades of evidence show that cash transfers can provide simple and effective protection against poverty, especially extreme poverty. A nationally representative survey conducted in Argentina between July and August 2022 indicates very high support (85%) for targeted cash transfers to children and adolescents. In addition, 94% support setting the value of the transfers to at least at the basic food basket. Finally, opinion is divided on eligibility criteria: slightly more than half (53%) support cash transfers targeting at least all children and adolescents living in poverty, while 45% prefer to restrict them to those living in extreme poverty.